GREEN CHILI PLANT RESULTS ON TYPES OF ORGANIC MULCH AND MANURE - Maryana, Maryana; Aulia, Nadya Rahma (Universitas Pembangunan Nasional Veteran Yogayakarta, 2024)
Improvement of cultivation techniques to increase green chili yield is by applying organic mulch and using manure. This study was to determine the best organic mulch and manure application for the growth and yield of green chili plants. The study was conducted in Pandes I, Wonokromo, Pleret, Bantul Regency, Special Region of Yogyakarta in March - June 2023. This study used a Split Plot Design with two factors in three replications. The main plot is the type of organic mulch consisting of 4 levels: rice straw, rice husks, sawdust, and bamboo litter. The subplot is the type of manure consisting of 3 levels: cow manure 30 tons/ha, goat manure 30 tons/ha, and chicken manure 30 tons/ha. The results showed that there was no interaction between the use of organic mulch and manure on all plant yield parameters. Organic mulch such as rice straw, sawdust, rice husks and bamboo litter did not give the best results on the total weight of green chili per plot, the weight of green chili per hectare and the harvest index of green chili. The use of chicken manure gave the best results on the weight of green chili per harvest, the total weight of green chili, the weight of green chili hectare, and the harvest index of green chili.